2017
DOI: 10.18632/oncotarget.22546
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates vascular smooth muscle cell function through downregulation of SIRT1

Abstract: BackgroundThere are sex differences in the incidence and severity of cardiovascular disease. Although an estrogen-mediated vasculoprotective effect is widely accepted, clinical trial results have been conflicting and the detailed mechanisms are still unclear. Sirtuin 1 (SIRT1), a class III histone deacetylase, may protect against vascular aging and atherosclerosis; however, the effects of estrogen on SIRT1 expression and vascular smooth muscle cell (VSMC) behavior remain unknown.Materials and MethodsWe ovariec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…SIRTs are a family of NAD + dependent histone/protein deacetylases highly conserved through bacteria and eukaryotes [ 111 ]. SIRT1 has been demonstrated to inhibit oxidative stress and inflammation [ 112 , 113 ] and deacetylates a wide range of substrates, including p53, NF-κB, FOXO transcription factors, Ku-70 and PGC-1 α, with roles in cellular processes ranging from energy metabolism to cell survival. Many studies in recent years have highlighted the correlation of SIRT1 activity with AMPK and mTOR pathway [ 114 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…SIRTs are a family of NAD + dependent histone/protein deacetylases highly conserved through bacteria and eukaryotes [ 111 ]. SIRT1 has been demonstrated to inhibit oxidative stress and inflammation [ 112 , 113 ] and deacetylates a wide range of substrates, including p53, NF-κB, FOXO transcription factors, Ku-70 and PGC-1 α, with roles in cellular processes ranging from energy metabolism to cell survival. Many studies in recent years have highlighted the correlation of SIRT1 activity with AMPK and mTOR pathway [ 114 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although production of estrogen declined dramatically in females after menopause status, the estrogen remained at moderately low level. SIRT1, possibly through the AKT and ERK signaling pathways, plays a crucial role in estrogen in protecting arteries from senescence and atherosclerosis [47]. Resveratrol also functions as a suppressor of PM-induced in ammatory signaling pathways by inhibiting COX-2/PGE2 expression [48].…”
Section: Discussionmentioning
confidence: 99%
“…This non-genomic regulation may explain our current results that CD38 gene deletion markedly increases SIRT1 protein levels without significant effect on its mRNA expression. Several studies demonstrated the down-regulation of SIRT1 protein levels by E2 treatment in vascular smooth muscle cells (16, 33), but there was no data showing that E2 had effects on SIRT1 gene expression. In the present study, E2 induced obvious decrease in SIRT1 mRNA and protein levels in WT ASMCs but not in CD38 KO cells, suggesting that other unknown mechanisms may exist in E2's actions associated with CD38 and warrants further investigation in our feature work.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens were shown to increase CD38 gene expression and leads to increased calcium mobilization and contractility of the myometrium (14, 15). It has also been recently reported that E2 downregulated SIRT1 expression in vascular smooth muscle cells, with increased apoptosis, reduced proliferation and migration, which were reversed by the SIRT1 activator Resveratrol (16). SIRT1 regulates p53-dependent apoptosis by deacetylating the Lys382 residue of p53, thus enhancing the transcriptional activity of p53 and inhibiting p53-induced apoptosis (17).…”
Section: Introductionmentioning
confidence: 91%